## Respuesta :

**Answer: **The correct answer is **b=2a**

**Step-by-step explanation:**

**Solve for b**

A = (a + b)/3

**Flip the equation**

1/3a + 1/3b = a

**Add (-1)/3a to both sides.**

1/3a + 1/3b + −1/3a = a + −1/3a

1/3b = 2/3a

**Divide both sides by 1/3**

(1/3b)/(1/3) = (2/3a)/(1/3)

**b=2a**

**Answer:**

[tex]b = 3A - a[/tex] (if A and a are two different variables).

[tex]b = 2a[/tex] (If the A and a denote the same variable.

**Step-by-step explanation:**

[tex]A = \frac{(a + b)}{3}[/tex]

Isolate the variable, b. Note the equal sign, what you do to the one side, you do to the other.

Do the opposite of **PEMDAS**. PEMDAS is the order of operations, and stands for:

**P**arenthesis

**E**xponents (& Roots)

**M**ultiplication

**D**ivision

**A**ddition

**S**ubtraction

~

First, multiply 3 to both sides of the equation:

[tex]A (*3) = \frac{(a + b)}{3} (* 3)\\A * 3 = (a + b)[/tex]

Next, subtract a from both sides of the equation:

[tex]A * 3 = a + b\\3A = a + b\\3A (-a) = a (-a) + b\\b = 3A - a[/tex]

[tex]b = 3A - a[/tex] is your answer.

IF, however, you meant to put both lower case variable a (or vice versa), then you can further simplify:

[tex]b = 3a - a\\b = 2a[/tex]

[tex]b = 2a[/tex] is your answer if the a are supposed to be the same variable.

Learn more about isolating a variable, here:

https://brainly.com/question/1730064